2020
DOI: 10.1002/ehf2.12597
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‐peripheral transvenous gradients of microRNA expression in systolic heart failure patients

Abstract: Aims The aims of the study are to assess the levels of coronary sinus (CS) miRNAs of systolic heart failure (HF) patients in samples obtained during cardiac resynchronization therapy (CRT) device implantation and compare them to the peripheral systemic venous miRNA expression. Methods and ResultsThe cardiac specific miRNA levels were assessed in 60 patients, 39 HF patients with reduced ejection fraction and 21 control patients. The levels of four cardiac specified miRNAs (miR-21-5p, miR-92b-3p, miR-125b-5p, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…No significant associations were found between miR-125b-5p and other clinical biomarkers. Higher circulating levels of miR-125b have been described in HF patients as compared with no-HF patients [ 22 , 29 , 42 ]. Interestingly, recent data suggest that miR-125b might be secreted by cardiac tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant associations were found between miR-125b-5p and other clinical biomarkers. Higher circulating levels of miR-125b have been described in HF patients as compared with no-HF patients [ 22 , 29 , 42 ]. Interestingly, recent data suggest that miR-125b might be secreted by cardiac tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among dysregulated miRNAs in CVD, miR-499 and miR-125b-5p have been closely involved in HF; both have been described as highly expressed cardiac miRNAs, which are released under stressful conditions [ 10 , 21 , 22 ] as well as good circulating biomarkers in HF [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-92b-3p, along with miR-133a-3p, is one of the cardiac specific miRNAs involved in heart failure (i.e., cardiomyocyte apoptosis, hypertrophy, and inflammation) and was reduced in the coronary sinus of patients with heart failure [ 58 ]. In particular, miR-92b-3p was observed to be decreased in mouse hypertrophic cardiomyocytes upon angiotensin II antagonist treatment and its overexpression can attenuate the hypertrophic phenotype by downregulating the hypertrophy related genes [ 58 60 ]. Mdx mice show a mild cardiomyopathy and, according to the literature, we found that at T16, miR-92b-3p in naive mdx plasma was downregulated compared to naive wt mice (FC = − 0.896, not significant).…”
Section: Resultsmentioning
confidence: 99%
“…MiR-92b-3p-DKK3 and miR-25-3p-TMEM184B were also identified in our study. Compared with the peripheral venous circulation, the level of expression was lower for miR-92b-3p in the coronary sinus of patients with heart failure ( 51 ). The expression level of miR-92b-3p was lower under the hypoxic condition, and it can inhibit proliferation and cell cycle progression in pulmonary arterial hypertension ( 52 ).…”
Section: Discussionmentioning
confidence: 99%